Transmission of multidrug-resistant Gram-negative bacteria from colonized mothers to their infants: a systematic review and meta-analysis. Issue 1 (January 2020) - Bulabula, A.N.H.; Dramowski, A.; Mehtar, S.
Summary: Background: Neonatal sepsis remains a leading cause of neonatal mortality. Maternal bacterial colonization plays a major role in transmission to the infant, with potential for subsequent development of neonatal sepsis with maternally derived strains. Aim: To review the molecular evidence supporting transmission of multidrug-resistant Gram-negative bacteria (MDR-GNB) from colonized mothers to their infants and the risk factors for MDR-GNB transmission. Methods: PubMed and Scopus were searched for studies investigating the mechanisms, risk factors for and/or scale of transmission of MDR-GNB from colonized mothers to their infants. Random effects meta-analyses were performed to determine pooled proportions of MDR-GNB transmission and the neonatal outcomes of transmission. Findings: Eight studies were included in the narrative description and six in the meta-analysis. Five studies used pulsed-field gel electrophoresis to assess relatedness of isolates from colonized mothers and their infants. Pooled proportion of MDR-GNB transmission from colonized mothers to their infants was 27% (95% confidence interval (CI): 8–47%). Extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae were the most frequently studied MDR-GNB pathogens transmitted between mother–infant pairs. Following mother-to-infant transmission of an MDR-GNB pathogen, the pooled proportion for the outcome of neonatal colonization was 19% (95% CI: 3–35%). Conclusion: This systematic review strongly supports MDR and/or ESBL Enterobacteriaceae transmission from colonized mothers to their infants, with subsequent infant colonization. The risk factors contributing to transmission of MDR-GNB between colonized mothers and their infants warrants further research.